PENETAPAN KADAR FLAVONOID TOTAL DARI EKSTRAK ETANOLIK DAUN BENALU MANGGA (Dendrophthoe pentandra L. Miq) - Rizki Yulianti R; A. Amaliah Dahlia; Aktsar Roskiana Ahmad (Faculty of Pharmacy, Universitas Muslim Indonesia, 2014)
Mistletoes (Dendrophthoe pentandra L. Miq) is one of the medicine plant which used traditionally to remedy the various of disease. Empirically, communities used mistletoes leaves as cough, tonsillitis, measles, cancer, diuretic, and pain relievers. This research is aimed to determine total flavonoid content in extract of mistletoes leaves (Dendrophthoe pentandra L. Miq). Extraction has done with Thin Layer Cromathography (KLT) method to determine active content which in sample. Analysis of chemistry content in ethanolic extract of mistletoes leaves show are flavonoid content. Content of total flavonoid with Chang et al., 2002 method using UV-Vis spectrophotometry at a wavelength of 440 nm. From this research result 39.713 g ethanolic extract with percent of extract rendamen is 6.109% from 650 g dry powder of mistletoes leaves. The results of total flavonoid of ethanolic extract of mistletoes leaves is 2.48% calculated as quercetin.